2011
DOI: 10.1038/emboj.2011.288
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPβ: lost beyond translation

Abstract: The mRNA 3′UTR has an important role in post‐transcriptional regulation. An article in this issue of The EMBO Journal describes a new role for mRNA 3’UTRs in regulating protein activity by controlling the localization of the C/EBPβ mRNA and spatially sequestering C/EBPβ from the kinases required for its activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The C/EBP b (also known as CEBPB) is a basic leucine zipper transcription factor that regulates a variety of biological processes, including metabolism, cell proliferation and differentiation, and immune response (11)(12)(13). Recent findings show that C/EBP binduced inflammatory responses mediate KA-triggered excitotoxic brain injury (10).…”
mentioning
confidence: 99%
“…The C/EBP b (also known as CEBPB) is a basic leucine zipper transcription factor that regulates a variety of biological processes, including metabolism, cell proliferation and differentiation, and immune response (11)(12)(13). Recent findings show that C/EBP binduced inflammatory responses mediate KA-triggered excitotoxic brain injury (10).…”
mentioning
confidence: 99%
“…The transcription factor CEBPB is a basic leucine zipper DNAbinding domain protein that regulates the proliferation and differentiation of various cell types. 38 Previous studies [39][40][41] have primarily focused on the critical role of CEBPB in cellular senescence. However, several studies [42][43][44] have also observed an association between CEBPB and pro-apoptotic processes.…”
Section: Discussionmentioning
confidence: 99%
“…In nasopharyngeal carcinoma and HNSCC, CEBPB is involved in PGC1α-mediated radiation resistance [ 17 , 34 ]. The abnormal translation of CEBPB [ 35 ] has been widely reported in macrophage migration [ 36 ], metabolic diseases [ 37 ] and leukemia [ 38 ]. EIF6 was previously described as a CEBPB translational regulator, mainly in adipogenic regulation [ 18 ].…”
Section: Discussionmentioning
confidence: 99%